Novel supercapacitor materials including OLED emitters. (2nd November 2015) - Kim, Seungho; Jang, Kihun; Park, Beom-Soo Michael; Ahn, Heejoon; Ko, Jang Myoun; Park, Jongwook
Abstract : This study constitutes the first attempt to use an OLED emitter material as a novel supercapacitor component. In supercapacitor tests, the specific capacitance (33.07 F g −1 ) of a poly(9-(3-vinyl-phenyl)-anthracene) (PVPA)/multi-walled carbon nanotube (MWCNT) mixture was found to be approximately three times that of the system composed of the MWCNTs alone. Abstract : This study constitutes the first attempt to use an OLED emitter material as a novel supercapacitor component. In supercapacitor tests, the specific capacitance (33.07 F g −1 ) of a poly(9-(3-vinyl-phenyl)-anthracene) (PVPA)/multi-walled carbon nanotube (MWCNT) mixture was found to be approximately three times that of the system composed of the MWCNTs alone.